2018
DOI: 10.1111/anae.14520
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of severe critical events in paediatric anaesthesia in the United Kingdom: secondary analysis of the anaesthesia practice in children observational trial (APRICOT study)

Abstract: The anaesthesia practice in children observational trial of 31,127 patients in 261 European hospitals revealed a high (5.2%) incidence of severe critical events in the peri-operative period and wide variability in practice. A sub-analysis of the UK data was undertaken to investigate differences compared with the non-UK cohort in the incidence and nature of peri-operative severe critical events and to attempt to identify areas for quality improvement. In the UK cohort of 7040 paediatric patients from 43 hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 25 publications
1
24
0
Order By: Relevance
“…The APRICOT study demonstrated an incidence of serious perioperative events of 5.2% of procedures, 12 which is much higher than our evaluation at 1.7%. However, a secondary analysis of the APRICOT data from the UK demonstrated a lower overall incidence of 3.3% 18 . Our evaluation differed from APRICOT, as patient numbers were much smaller and it did not cover the full spectrum of pediatric anesthetic practice.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The APRICOT study demonstrated an incidence of serious perioperative events of 5.2% of procedures, 12 which is much higher than our evaluation at 1.7%. However, a secondary analysis of the APRICOT data from the UK demonstrated a lower overall incidence of 3.3% 18 . Our evaluation differed from APRICOT, as patient numbers were much smaller and it did not cover the full spectrum of pediatric anesthetic practice.…”
Section: Discussionmentioning
confidence: 91%
“…However, a secondary analysis of the APRICOT data from the UK demonstrated a lower overall incidence of 3.3%. 18 Our evaluation differed from APRICOT, as patient numbers were much smaller and it did not cover the full spectrum of pediatric anesthetic practice. However, the commonest severe critical event reported in APRICOT was laryngospasm, which occurs in all aspects of pediatric anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…The APRICOT has also shown that senior anesthesiologists had 1% fewer critical respiratory events per year of experience and that facilities with a higher caseload had a lower rate of critical events [17]. A sub-analysis using the UK data only in the APRICOT demonstrated that the lower incidence of cardiovascular and respiratory complications could be partly attributed to more experienced dedicated pediatric anesthesia providers managing the higher-risk patients, whereas it did not show significant inverse volume-outcome effects in perioperative critical events among institutions [26]. Hence, controversies in volume-outcome association per anesthesia provider or per institution in terms of the incidence of perioperative adverse events exist.…”
Section: Volume-outcome Association In Pediatric Anesthesiamentioning
confidence: 97%
“…The concept of "making every moment count" is important. Meanwhile, lack of experiences and clinical exposures may result in less independent practices and loss of self-confidence of anesthesiologist trainees, eventually leading to increasing perioperative complications and growing concerns over patient safety [17,25,26].…”
Section: Recent Changes Impacting On Anesthesia Training In Japanmentioning
confidence: 99%
“…Another major contributing factor affecting outcomes, frequently not considered, is the (in-) experience of anaesthesia care provider and subsequent clinical conduct of anaesthesia in these vulnerable patients [16,31,32]. Competent delivery of perioperative anaesthesia care in a suitably staffed environment may reduce the risk of occurrence of severe perioperative complications [33].…”
Section: Factors That May Affect Medical Outcomesmentioning
confidence: 99%